Crystal engineering of coordination-polymer-based iodine adsorbents using a π-electron-rich polycarboxylate aryl ether ligand. Issue 40 (1st October 2020) - Chen, Junling; Li, Bo; Shi, Zhenzhen; He, Cheng; Duan, Chunying; Zhang, Tiexin; Wang, Li-Ya
Abstract : This work revealed that the synergy of microporous channels and convergent arrangements of halogen bonding and charge-transfer interaction sites within coordination polymers facilitated the iodine adsorption process. Abstract : Efficient capture and storage of radioactive iodine isotopes are important in nuclear waste treatment and environmental protection. Coordination polymers (CPs) are a family of newly emerging potential iodine adsorbents. However, the exact structure–activity relationship between various structural CP hosts and their noncovalent adsorption effects toward iodine guest molecules has not been elucidated. Herein, a crystal engineering strategy was employed to systematically study the effects of porosity and arrangement of noncovalent interaction sites of CP hosts on the iodine uptake performance. Three isomeric CPs—{[Zn3 (μ3 -OH)(L)(H2 O)3 ]·2H2 O} n (1 ), {[Zn3 (μ3 -OH)(L)(H2 O)]·2DMF·3H2 O} n (2 ), and {[Zn3 (μ3 -OH)(L)(DMF)2 ]·H2 O} n (3 )—having different structures were synthesized from a π-electron-rich polycarboxylate ligand, H5 L [5, 5′-((5-carboxy-1, 3-phenylene)bis(oxy))diisophthalic acid], containing potential sites for charge-transfer interaction and halogen bonding. CP 2, with a medium channel size and suitable arrangement of noncovalent interaction sites, exhibited higher I2 adsorption capacity than the other two CPs. The synergistic CO⋯I and charge-transfer π⋯I interactions between the I2 guest and the carboxylate moiety and the benzene ring of CP 2, respectively, were validated by X-ray diffraction analysis, electrochemical impedance spectroscopy, and solid-state fluorescence spectroscopy.